Analisis Menurunnya Kinerja Fresh Water Generator Di Kapal MV. Dream Orchid Dengan Metode Root Cause Analysis - Nawirudliya, Muhammad; Gunarti, Monika Retno; Ratnaningsih, Dyah; Nugroho, Aziz; Zainuddin, Mochammad (Universitas Pahlawan Tuanku Tambusai, 2025)
The long duration of the voyage necessitates the availability of sufficient fresh water on board. The fresh water generator (FWG) is an auxiliary device that functions to produce fresh water by converting seawater into fresh water through evaporation and condensation processes. The importance of FWGs in onboard operations has prompted researchers to examine their performance in meeting freshwater needs. This research was conducted to determine the factors contributing to the decline in FWG performance, its impacts, and the measures taken to address these issues.The research method used is qualitative descriptive, with data collected through observation, interviews, documentation, and literature review. The research data is then analyzed using Root Cause Analysis (RCA) to identify and examine the root causes of problems or failures.The results of the study indicate that the decline in FWG performance is caused by several factors, including improper maintenance, operation not following standard procedures, and muddy seawater conditions. Additionally, the aging of pipe materials reduces resistance to corrosion. Another contributing factor is the decrease in engine efficiency and performance due to prolonged operating hours. The impact of reduced FWG performance is a decline in freshwater production on board.To optimize FWG performance, routine maintenance should be carried out according to operational schedules, coordination regarding the FWG’s condition before and after maintenance should be improved, and periodic evaluations of maintenance effectiveness should be conducted to determine more efficient steps for the future.